Konstruksi Pendidikan Karakter Pondok Pesantren Berbasis Kearifan Lokal di Banten - Mada Indramawan; Machdum Bachtiar; Fandy Adpen Lazzavietamsi; Wawan Wahyuddin; Wasehudin (Jurnal Ilmiah Edukatif, 2024)
Anxiety about the rapid flow of globalization raises anxiety about the fading of religious values in students so that character education is very important because it has a positive impact on student character, as well as to deal with the rapid flow of globalization which presents many rapid changes that are very difficult to accept and follow. The condition of Banten society in general has experienced many shifts in values and character, especially in the younger generation. The shift in values and character occurs due to many factors, one of which is the weakening of character education. This research uses a qualitative research method with a literature study approach. In literature review research, researchers conducted a study of several existing theories and concepts to form a conclusion construction to find out about the construction of character education based on pesantren local wisdom in Banten City. Indicators of character education are said to be good with an increase in the spiritual intelligence of the individual. The nature of istiqomah in a person can provide changes that will produce an understanding and gain new insights. In addition, the nyantri tradition is also a local wisdom found in the city of Banten.